LEKSIKOLOGI KOSAKATA FAUNA BAHASA KAMBERA - Raynesta Mikaela Indri Malo; Itha Priyastiti (Universitas Warmadewa, 2024)
Linguistic studies show that half of the world's languages ??are on the verge of extinction, meaning they are no longer passed down to younger generations. One of the causes of language extinction is the minimum number and quality of documentation of local languages. Therefore, maintaining language as a form of preserving the culture of a society is very important. This research was conducted to document the Kambera language, especially the fauna lexicon including the names of livestock, poultry, and non-livestock or other wild animals in East Sumba. The aim of this research is to produce a list or inventory of the fauna in the Kamberan language. The results of this research are expected to become a form of language documentation for the Kambera language in order to support language maintenance. This research is a lexicological study that uses qualitative methods and data collection is done through observation, interviews, and documentation. Data were analyzed using the equivalent method with the determinant being the referent and another language, namely Indonesian. The results of the data analysis found 60 names of fauna and grouped by type of fauna, (1) livestock, (2) poultry, (3) birds (birds), (4) pets, (5) animals that live in water, (6) reptiles, and (7) other animals.